In vitro antifungal activities of C. sativum and C. aurantifolia against Aspergillus sp. of onion bulbs / Nurul Aimi Syazana Baba ... [et al.] - Baba, Nurul Aimi Syazana; Hashim, Saiyidah Nafisah; Rodzali, Nur Nadirah; Abdullah, Siti Nur Azmu’i; Muhammad, Noor Amira (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Phytopathogenic fungi have been a mass problem in agriculture, including black mould disease in Allium cepa. The study objective is to find the antifungal potential of Coriandrum aurantifolia and Citrus sativum against fungal species isolated from onion bulbs. Thus, the antifungal activity of both leaf extracts of C. aurantifolia and C. sativum alone or in combination at different ratios were tested in this study using the food poisoned technique. Phytochemical screening showed that the C. aurantifolia leaf extract has more active metabolites than C. sativum. C. aurantifolia contains all active constituents tested except terpenoids. Infected A. cepa with black mould was used, and the infection was isolated. According to morphological characteristics, fungal was identified as Aspergillus sp. Antifungal activity discovered a synergistic effect between 100 mg/mL of leaf extract (T8), resulting in the highest reduction of mycelial growth and inhibition percentage. The results concluded that C. aurantifolia and C. sativum leaf have potential antifungal applications and are synergistically effective in preventing the growth of Aspergillus sp. They provide a better reduction in mycelial growth than the positive control. The phytochemical compounds in both extracts might contribute to fungal inhibition activities. To conclude, these two extracts were beneficial as a natural antifungal for Allium cepa.